15 GHz grid array antenna for 5G mobile communications system - Sani Yahya, M. (John Wiley and Sons Inc., 2016)
A compact grid array antenna implemented using FR4 substrate for 5G Mobile Communications at 15 GHz is presented. The antenna with dimensions of 49 mm × 58 mm × 1.6 mm has 23 radiating elements to provide high gain. It is excited using coaxial feeding technique. Measurement of the fabricated prototype for the simulated antenna was carried out. Both measured and simulated results agree with each other. The measured result shows that the antenna has achieved an impedance bandwidth of 14% from 13.8 GHz to 15.9 GHz with a gain of 14.4 dBi at 15.9 GHz.